The mediating role of brand experience on product quality, service quality and consumer resonance of favourite fast food brand / Rozita Naina Mohamed, Norzaidi Mohd Daud and Rosidah Musa - Naina Mohamed, Rozita; Mohd Daud, Norzaidi; Musa, Rosidah (Division of Research, Industrial Linkages and Alumni, UiTM Cawangan Melaka, 2011)
Despite the importance of the Local Fast Food market segment and the growing revenues, nevertheless, not much has been done to understand on local home-grown fast food brand consumers. This study samples customer’s fast food consumption experience from their most favourite fast food brand in Malaysia by using quota sampling. The presentation of the sample’s demographic statistical descriptive analyses is based on frequency scores and percentages. An evaluation of mean scores and standards deviation of scale measurements for key hypothesized constructs will also be undertaken. The results provide an insight into the practical implications that could influence successful implementation of branding models specifically for the local home-grown fast food industry. Indeed, it could also unveil the opportunity for the chained fast food businesses even for Asian or Western fast food to reformulate their branding strategies to increase its revenues and earnings in today’s competitive environment.